Correlation between psychological diagnosis (Rorschach Psycho-diagnostics) and clinical diagnosis (Journal of Psychiatrists' Association of Nepal, 2023)
Background: A wide acceptance of the Rorschach test is shown in clinical practice and clinicians choose the test not only as a diagnostic instrument but as a therapeutic practice also, sometimes variety of opinion comes from health professionals and the validity of the test result become more challenging. It creates a cognitive dilemma and the clinician has two options: either choice to accept or reject the diagnosis.Material & Methods: A total 80 cases were selected from the psychiatry ward and written informed consent was taken. Socio-demographical data sheet was applied. Without knowing the history and other diagnostic variables, the Rorschach test was administered to make a psychological diagnosis by a qualified clinical psychologist and the clinical diagnosis was made through ICD-10 DCR criteria by the competent psychiatrist.Results: Among the participants, 37.5% belonged to 29-39 years age group; 58.75% were male. Most of the study samples were married (71.25%), 32.5% were educated up to 6-10th standard. The majority (38.75%) of the participants were unemployed and 51.25% belonged to rural areas. A majority, ie: 47.5% were in the middle-income group (50-74K) and living in a nuclear family (83.75%). Schizophrenia was the most frequent diagnosis in both categories, 38.75% belonging to the Rorschach diagnosis and 33.75% in the clinical category followed by Depression, mania, anxiety, obsession, psychosis, organic, and conversion disorder. Overall, a high correlation was found between both diagnostic categories (X2 =4.1, P=0.75). Conclusion: The findings of the study suggest that a high level of correlation was found between clinical diagnosis and Rorschach psycho-diagnosis.